2007
DOI: 10.1111/j.1463-1318.2007.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection of diverticular fistulae: a 10‐year experience

Abstract: Totally laparoscopic resection for diverticular fistulae is safe and feasible. Fistulae should not be considered as a contraindication to laparoscopic resection for an experienced laparoscopic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
1
34
0
3
Order By: Relevance
“…11 More recent studies have demonstrated morbidity rates between 12% and 15%. [12][13][14] The current study demonstrated an overall morbidity rate of 20%, with no major complications or laparoscopy-related complications. There was a higher rate of complications in converted patients (40% versus 11% for nonconverted), but this was not statistically significant (P ¼ 0.925).…”
Section: Laparoscopic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…11 More recent studies have demonstrated morbidity rates between 12% and 15%. [12][13][14] The current study demonstrated an overall morbidity rate of 20%, with no major complications or laparoscopy-related complications. There was a higher rate of complications in converted patients (40% versus 11% for nonconverted), but this was not statistically significant (P ¼ 0.925).…”
Section: Laparoscopic Managementmentioning
confidence: 99%
“…[4][5][6][7] A review of the literature indicated very few studies on the laparoscopic management of diverticular colovesical fistulas exist. 4,8,9 The outcomes of recent studies are difficult to interpret as many have incorporated both recurrent uncomplicated and complicated disease, have not differentiated between colovesical fistulas and other diverticular fistulas, [10][11][12][13][14][15] or have included fistulas of various aetiologies. [16][17][18][19][20] Other studies have not used a total laparoscopic approach but have performed technically challenging aspects with a resection-facilitated or hand-assisted technique.…”
mentioning
confidence: 99%
“…18,19,20 Conforme as equipes adquirem maior experiência os resultados são melhores e as contra-indicações menores. Um estudo multicêntrico prospectivo com 1545 pacientes separou os centros participantes em três grupos de acordo com o volume operatório em ressecções por doença diverticular (grupo I > 100 casos; grupo II 30-100 casos; grupo III < 30 casos).…”
Section: Acesso Cirúrgico Na Urgênciaunclassified
“…18,19 Nestes casos a curva de aprendizado parece influenciar significativamente o índice de conversões. Um grupo britânico divulgou seus resultados com 31 pacientes (22 com fístula colovesical e nove com fístula colovaginal) submetidos à sigmoidectomia LAP em um período de 11 anos.…”
Section: Tabela 3 -Redução Na Incidência De óBitos E Estomias E Econounclassified
See 1 more Smart Citation